ROLE OF THE UNHCR IN REPATRIATION OF AFGHAN REFUGEES FROM PAKISTAN: POST 9/11 ERA - Faiz Bakhsh; Muhammad Asif Safdar (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
The post 9/11-armed conflict in Afghanistan resulted in the displacement of millions of Afghans and many of these displaced persons entered Pakistan as refugees. Repatriation is considered as a durable solution of the refugee problem. It is the responsibility of the host state to plan for safe and voluntary return of refugees and the UNHCR plays a supportive role in complying with this responsibility. Despite, efforts of the Government of Pakistan in collaboration with the UNHCR, Afghan Refugees keep struggling in getting repatriated. UNHCR has been helping and assisting the government of Pakistan in planning and executing the safe and voluntary Afghan refugees under international legal framework. Although, this cooperation between the UNHCR and Pakistan has remained effective in achieving the goal of repatriation of Afghan Refugees in the context of ongoing conflicts in both Afghanistan and Pakistan in the context of difficult circumstances, however, the achievement of a safe and voluntary return of Afghan Refugees remains a big issue in this process. To comply with the legal framework for refugees regarding repatriation, Pakistan had been struggling a lot in the context of the ongoing armed conflict in both Afghanistan and Pakistan. This paper discusses the repatriation of the Afghan refugees from Pakistan, engineered by the UNHCR and Pakistan, under the legal framework applicable for safe and voluntary return of refugees, amid waves of repeated displacements due to the ongoing conflicts in Afghanistan and Pakistan. Abstrak: Konflik bersenjata pasca 9/11 di Afghanistan mengakibatkan perpindahan jutaan orang Afghanistan dan banyak dari orang-orang terlantar ini memasuki Pakistan sebagai pengungsi. Repatriasi dianggap sebagai solusi jangka panjang dari masalah pengungsi. Hal ini merupakan tanggung jawab negara tuan rumah untuk merencanakan pemulangan pengungsi yang aman dan sukarela. Disini UNHCR memainkan peran pendukung dalam memenuhi tanggung jawab ini. Meski demikian, upaya pemerintah Pakistan bekerja sama dengan UNHCR, Pengungsi Afghanistan terus berjuang untuk dipulangkan. UNHCR telah membantu pemerintah Pakistan dalam merencanakan dan melaksanakan pemulangan pengungsi Afghanistan dengan aman dan sukarela di bawah kerangka hukum internasional. Meskipun kerjasama antara UNHCR dan Pakistan ini tetap efektif dalam mencapai tujuan pemulangan pengungsi Afghanistan, namun dengan konflik yang sedang berlangsung di Afghanistan dan Pakistan membuat hal ini sangat sulit. Oleh karena itu, pemulangan yang aman dan sukarela dari Pengungsi Afghanistan tetap menjadi masalah besar dalam proses ini. Untuk mematuhi kerangka hukum bagi pengungsi mengenai repatriasi, Pakistan telah banyak berjuang dalam menghentikan konflik bersenjata yang sedang berlangsung baik di Afghanistan dan Pakistan. Artikel ini membahas repatriasi pengungsi Afghanistan dari Pakistan, yang direkayasa oleh UNHCR dan Pakistan, di bawah kerangka hukum yang berlaku untuk pemulangan pengungsi konflik dengan aman dan sukarela. Hal ini terasa sulit di tengah gelombang perpindahan berulang karena konflik bersenjata berlangsung di Afghanistan dan Pakistan. Kata Kunci: Pengungsi Afghanistan, UNHCR, Pengungsi Pakistan, Pemulangan